2013
DOI: 10.1164/rccm.201205-0851oc
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial Pten Controls Acute Lung Injury and Fibrosis by Regulating Alveolar Epithelial Cell Integrity

Abstract: Our results highlight epithelial Pten as a crucial gatekeeper controlling ALI and lung fibrosis by modulating AEC integrity, and the Pten/PI3K/Akt pathway as a potential therapeutic target in these intractable diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
79
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(84 citation statements)
references
References 45 publications
3
79
2
Order By: Relevance
“…Exactly how this pattern of inhibition is achieved is unclear, but the inhibitory effects of methacycline on several non-Smad pathways imply that methacycline is acting very proximally in TGF-b1 signaling. The observed protective effects of inhibition of the non-Smad arm of TGF-b1 signaling is consistent with prior reports that Jun kinase, phosphoinositide 3-kinase (PI3K)/Akt, and p38 activities are each required for damaging fibrogenesis after bleomycin-induced lung injury (20,32,33). In addition, consistent with our observations, mice deficient in Jun kinase show suppression of fibrosis, but not inflammation after bleomycin-induced injury (32).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Exactly how this pattern of inhibition is achieved is unclear, but the inhibitory effects of methacycline on several non-Smad pathways imply that methacycline is acting very proximally in TGF-b1 signaling. The observed protective effects of inhibition of the non-Smad arm of TGF-b1 signaling is consistent with prior reports that Jun kinase, phosphoinositide 3-kinase (PI3K)/Akt, and p38 activities are each required for damaging fibrogenesis after bleomycin-induced lung injury (20,32,33). In addition, consistent with our observations, mice deficient in Jun kinase show suppression of fibrosis, but not inflammation after bleomycin-induced injury (32).…”
Section: Discussionsupporting
confidence: 92%
“…Recent evidence linking signaling pathways promoting EMT in vitro with fibrogenesis in vivo supports an important role for EMT signaling in fibrosis (5,6,(17)(18)(19)(20)(21)(22). Moreover, epithelial-specific expression of the canonical EMT transcription factor, Snail1, is required for experimental hepatic fibrosis (23).…”
mentioning
confidence: 98%
“…It is also surprising that Fgf2 2/2 mice do not have increased amounts of bleomycin-induced pulmonary fibrosis, as a link between epithelial injury and fibroproliferation in response to bleomycin is well described (57)(58)(59). For example, epithelial-specific knockout of b-catenin causes increased epithelial injury in response to bleomycin, and subsequently leads to increased fibrosis (58).…”
Section: Our Results Show That Fgf2mentioning
confidence: 99%
“…Mice with constitutive deficiency of PTEN develop spontaneous fibrosis by intrinsic defects in fibroblasts and negative regulation of their proliferative response (51,52). Furthermore, conditional targeted deletion of PTEN in lung epithelium exacerbated injury and fibrosis after bleomycin treatment by an increase of active TGF-β and loss of epithelial integrity (53). In support of a role for PTEN in PINK1 deficiency in IPF lungs, microarray analyses of the Lung Genomics Research Consortium (LGRC) cohort (http://www.lung-genomics.org/) showed that PINK1 expression correlated directly with expression levels of the gene set of the PTEN pathway (Supplemental Table 3).…”
Section: C) Mitochondrial Morphology In Pink1mentioning
confidence: 99%